The Present Study Investigates The Relationship Between Age And Working Period With The Occurrence Of Respiratory Disorder Symptoms In Wood Saw Operators In Bondowoso Regency 2023 - Fatah, Roiful; Nafisah, Khilda Durrotun (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
The timber industry in Indonesia is undergoing a period of growth, which has a positive impact on society by creating employment opportunities. However, this practice also exerts a detrimental effect on the environment, leading to pollution that adversely impacts the health of workers, including respiratory disorders caused by sawdust. The etiology of respiratory disorders is multifactorial, with age and length of service being salient contributors. The objective of this study is to examine the correlation between age and the duration of employment, on the one hand, and the incidence of respiratory symptoms among wood sawing workers in Bondowoso Regency on the other. The population of this study comprised 84 workers who met the inclusion and exclusion criteria. The present study employed a quantitative research method, incorporating cross-sectional. The findings of the research employing bivariate analysis demonstrated that the age of wood saw workers exhibited a p-value of 0.007, which is less than 0.05. The results of experience yielded a p-value of 0.001, which is less than 0.05, thereby indicating a significant association with the occurrence of respiratory symptoms. The study's recommendations to mitigate the occurrence of respiratory symptoms include the utilization of PPE masks, the consumption of nutritionally balanced meals, and the observation of activity patterns through regular exercise.